Indonesian Legal Approach of The Implementation of Tax Amnesty - Ferry Ferry (Fakultas Hukum, Universitas Internasional Batam, 2018)
The Purpose of this research is to see the implementation of the Tax Amnesty program in Indonesia and how will it be giving Advantages and Disadvantages to Indonesia. This final project produce some perspective from the author about what matters with the impact of this implementation of Tax Amnesty program to Indonesia from what are the reasons and purposes of this programs up to the reactions of all the citizens to this program. And in this final project, there will also be some other perspective from different parties such as lawyers, government, and also citizens that take part in the Tax problems. These research found that there are some conspiracy between how peoples react on the implementation of the program showing how they most likely disagree with the program and also from the other side. How government giving out their reason why they are still urging this program even though they know all the chaos going on in the public. This paper also produce arguments purely base on author’s idea of thinking and base on various of theories and mindsets from law experts, reasoning out that how author will judge the situation and all the cases took place in Indonesia regarding the implementation of Tax Amnesty program in Indonesia.